Continuous Improvement of the Requirements Engineering Process in a R&D Project - Silva, Luã; Portela, Carlos; Lisbôa, Rodrigo; Souza, Alinne; Souza, Francisco; Cordeiro, Thiago; Lobato, César; Fülber, Heleno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
This study reports on the experience of improving Requirements Engineering (RE) of a Research and Development (R&D) project aimed at developing a platform for text analysis using Artificial Intelligence (AI). Initially, some issues were identified, including unclear requirements, ineffective communication among stakeholders, and inadequate documentation. To address these challenges, we implemented the expected results of the Reference Model for Software Process Improvement (MR-MPS-SW) to guarantee quality in the RE practices followed. The results indicate a significant reduction in requirement changes, increased stakeholder satisfaction, and improved clarity of documentation. Finally, it is concluded that the implemented improvements contributed decisively to the project’s success, providing valuable insights for future R&D projects.